WELFARE LEVEL ANALYSIS AND HOUSEHOLD SATISFACTION LEVEL TARGETS RECIPIENT BENEFIT PROGRAM RASKIN - Muhammad Thamrin; Desi Novita; Dinda Ardrina Tanjung (AGRIUM: Jurnal Ilmu Pertanian, 2017)
The aim of this study was to analyze the welfare level and satisfaction level of the target households as the beneficiaries (RTS-PM) of the Raskin (Rice Poor) Program. The research was conducted in Batu Malenggang village, Kecamatan Hinai, Kabupaten Langkat. This research used descriptive statistic method, Costumer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Attributes analyzed program is the right  quantity, right price, right time, right quality and right administration. The results of research showed that: (1) the welfare level of household is measured by comparing the average household expenditure per capita Rp/month with the poverty line of Langkat (Rp 294.175/capita/month) is the household who has welfare level categorized as poor as much as 39 households, or 54,9%, and as 32 households or 45,1% in the category of not poor. (2) based on the calculation of the degree of correspondence between performance and expectations with methods IPA which attributes most eligible program (94%) is the "right price: payment Price redeem Raskin (HTR) is Rp 1.600/kg", and the attributes of the lowest levels of compliance/less suitable (22%) between the performance and the expectation is "the right quantity: the quantity of rice 15kg/RTS/month for 12 months". (3) The level of respondent satisfaction Raskin thoroughly for all attributes Raskin Program is categorized quite satisfied with the index of 55%. Keywords: Welfare, Satisfaction, RTS-PM, Raskin Program